Pet Rescue Adventures: The Mystery Kitten - Webb, Holly; Williams, Sophy (Wilton, CT : Tiger Tales, 2020)
After her family moves, Elsa is finding it difficult to make new friends. Then she hears strange, scratching noises at night and discovers a kitten living in the attic! The little cat has beautiful black fur so Elsa names him Pepper. Elsa is desperate to keep her new kitten friend. Dad thinks Pepper belongs to the previous owner, but who would leave behind such a beautiful kitten?--
Keywords: Kittens -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Animal Fiction